The emotion thesaurus : a writer's guide to character expression - Ackerman, Angela, ....-; Puglisi, Becca, ....- ([s.l.] : Jadd Publishing, 2019)
The bestselling Emotion Thesaurus, often hailed as “the gold standard for writers” and credited with transforming how writers craft emotion, has now been expanded to include 55 new entries! One of the biggest struggles for writers is how to convey emotion to readers in a unique and compelling way. When showing our characters' feelings, we often use the first idea that comes to mind, and they end up smiling, nodding, and frowning too much. If you need inspiration for creating characters' emotional responses that are personalized and evocative, this ultimate show-don't-tell guide for emotion can help. It includes: Body language cues, thoughts, and visceral responses for 130 emotions that cover a range of intensity from mild to severe, providing innumerable options for individualizing a character's reactions A breakdown of the biggest emotion-related writing problems and how to overcome them Advice on what should be done beforedrafting to make sure your characters' emotions will be realistic and consistent Instruction for how to show hidden feelings and emotional subtext through dialogue and nonverbal cues And much more! The Emotion Thesaurus, in its easy-to-navigate list format, will inspire you to create stronger, fresher character expressions and engage readers from your first page to your last.